Ranking of spring bread wheat genotypes according to the heading date and growing season duration in different ecogeographic environments - L. Yu. Novikova; E. V. Zuev; A. N. Brykova (Труды по прикладной ботанике, генетике и селекции)
Background. Adaptation of spring bread wheat cultivars to climate change requires a study of the factors affecting the length of their growing season in various environments. An attempt is made to analyze regularities in the effect of ecogeographic conditions on the correlations shown by the duration of the growing season and interphase periods in spring bread wheat genotypes.Materials and methods. Correlation coefficients were studied for the impact of the environment and temperature on the duration of the interphase periods from sprouting to heading (SH) and from heading to yellow ripeness (HR) versus the period from sprouting to yellow ripeness (SR) in VIR’s wheat collection across 18 sites located in Russia and Uzbekistan from 41 to 60°N and from 30 to 135°E. The effect of the genotype and year on SH and HR was studied, and agrometeorological regression models of SH and HR were constructed, based on the data obtained during the studies of the collection in St. Petersburg in 1945–2021.Results. For the sites below 52–54°N, the SR/SH correlation coefficient was generally higher than SR/HR, and in the upper latitudes it was vice versa. The change in the ratio of coefficients occurred due to an increase in the interannual variability of HR at lower temperatures. The effect of HR on SR became greater than that of SH at temperatures below 18°С during HR. The data of a long-term study in St. Petersburg demonstrated that the effect of the genotype on SH was 18.9%, with 68.9% of the year, and the effect of the factors on HR was 4.1 and 71.3%, respectively. Regression models showed that HR was determined by temperature for at least 81%, while SH had a lower coefficient of determination by weather (56%).Conclusion. Ranking of wheat genotypes according to their heading time reflected their differentiation in earliness. A significant contribution of HR was conspicuous under temperatures below 18°C after heading at latitudes above 52–54°N.